2007
DOI: 10.4102/jsava.v78i3.302
|View full text |Cite
|
Sign up to set email alerts
|

The toxicity of Senecio inaequidens DC.

Abstract: This study was designed to confirm the toxicity of a plant implicated in an outbreak of poisoning of stock in Frankfort, Free State Province, South Africa. Cows died acutely after being introduced into a camp, where an abundant, green shrublet was noted to be heavily grazed. This plant was subsequently identified as Senecio inaequidens DC. (Asteraceae) by the South African National Biodiversity Institute (SANBI). Extraction and chemical analyses for pyrrolizidine alkaloids (PAs) in Senecio inaequidens revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 53 publications
2
17
0
Order By: Relevance
“…This has also been observed in Cynoglossum officinale from the Boraginaceae plant family containing PAs where the highest alkaloid contents were in the inflorescences and young rosette leaves (Van Dam et al 1995). Similarly, the highest alkaloid contents were found in the inflorescences of various Senecio species (Chizzola et al 2010, Dimande et al 2007, Hartmann and Zimmer 1986). In the same way young Colchicum autumnale leaves contained more colchicine than later in the growing season (Winter et al 2013).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This has also been observed in Cynoglossum officinale from the Boraginaceae plant family containing PAs where the highest alkaloid contents were in the inflorescences and young rosette leaves (Van Dam et al 1995). Similarly, the highest alkaloid contents were found in the inflorescences of various Senecio species (Chizzola et al 2010, Dimande et al 2007, Hartmann and Zimmer 1986). In the same way young Colchicum autumnale leaves contained more colchicine than later in the growing season (Winter et al 2013).…”
Section: Discussionmentioning
confidence: 55%
“…The identified alkaloids were already reported in literature. Retrorsine and senecionine were the main alkaloids in South African plants (Dimande et al 2007). Similarly, Wiedenfeld et al (1981) found 0.21 % retrorsine and 0.064% senecionine in S. inaequidens.…”
Section: Discussionmentioning
confidence: 96%
“…The high concentration (12000 µg/g) of unsaturated PAs detected in the plant implicated this Senecio species as the cause of toxicity and the presence of the toxic PAs in the rumen content confirmed exposure of the cows. The diagnosis of PA poisoning was corroborated by histopathological evidence of diffuse centrilobular to submassive necrosis and haemorrhage in liver samples collected from the dead cows (Dimande et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Crotalaria sphaerocarpa seeds were collected from a maize farm 2 km north of Oberholzer in (Dimande et al, 2007). Necropsies were performed on cattle that have died and rumen content (500 g) was collected and submitted for analysis together with the collected plant material.…”
Section: Plant Samples and Rumen Contentmentioning
confidence: 99%
“…Giunti et al 2015)]. This species causes ecological, economical and social impacts: loss of biodiversity (especially in meadows and pastures, see Giunti et al 2015), reduction in productivity and quality of cultivated lands (especially wineyards, see Banfi & Galasso 2010: 248), and threats to the health of humans and domesticated animals (cows, horses, and sheeps) on account of its a high concentration of toxic pyrrolizidine alkaloids, which are passed also through milk and honey (see e.g., Dimande et al 2007). Giunti et al (2015) Photos: Danin (2015).…”
Section: Photos: Bgfloranet (2009)mentioning
confidence: 99%